2001
DOI: 10.1366/0003702011952127
|View full text |Cite
|
Sign up to set email alerts
|

Curve Fitting and Linearity: Data Processing in Raman Spectroscopy

Abstract: A study has been made of the use of polynomial curve fitting for removal of nonlinear background and high-spatial-frequency noise components from Raman spectra. Two variations on polynomial curve fitting through a least-squares calculation are used. One, involving fitting data x values to corresponding y values, was used to approximate background functions, which are subtracted from the original data. For smoothing, a reference matrix of six vectors that contains a unity d.c. level, a ramp made up of x values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 2 publications
2
63
0
Order By: Relevance
“…A Raman spectrum is collected for each A-scan but because of poor signal to noise the spectra are generally averaged over neighboring samples. The spectrum have a polynomial fit subtracted to remove florescence following the technique of Vickers et al 15 The intensity of the spectrum has not been calibrated to correspond to the amount of any particular substance in the sample so the spectrum are shown with an arbitrary scale.…”
Section: Resultsmentioning
confidence: 99%
“…A Raman spectrum is collected for each A-scan but because of poor signal to noise the spectra are generally averaged over neighboring samples. The spectrum have a polynomial fit subtracted to remove florescence following the technique of Vickers et al 15 The intensity of the spectrum has not been calibrated to correspond to the amount of any particular substance in the sample so the spectrum are shown with an arbitrary scale.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have found that a fifth-order polynomial best approximates the shape of the background. [4][5][6][7] However, because of the inevitable introduction of spectral artifacts, some researchers have found that removing the background does not improve calibration results obtained from multivariate analysis. 8 …”
Section: Background Signal In Biological Raman Spectramentioning
confidence: 99%
“…These methods can be divided into two categories: manual and automatic techniques. In the manual method [1], the baseline is constructed by using linear, polynomial, or spline functions fitted on the no signal (baseline) points selected by users. If the points are correctly selected, the construction would produce satisfactory results.…”
Section: Introductionmentioning
confidence: 99%